Implementasi Pembelajaran Pendidikan Agama Islam (PAI) Kelas Digital di SMP IT Al Huda Wonogiri - Ilham Khoirudin; Uswatun Khasanah; Ahans Mahabie (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
This study discusses the Implementation of Digital Islamic Religious Education Learning at SMP IT AL HUDA Wonogiri. The purpose of this study was to find out how the process of implementing Islamic religious education learning in digital classes, the supporting factors and obstacles faced by teachers and students in implementing digital classes as well as advantages and disadvantages during the implementation of digital classes in learning. This study uses a qualitative approach. Data collection uses observation techniques, interviews with the head of the digital class organizer, Islamic religious education subject teachers, 8th grade male and female students, and documentation. The results of research conducted by researchers are as follows: 1). The implementation of Islamic religious education learning using digital classes at SMP IT AL HUDA is a learning model using digital supporting tools, such as laptops, LCDs, projectors, sound systems, etc. The media used in learning such as Ms. Teams, Quizizz, Teacher Room, Youtube, ZoomMeet etc. The goal in the form of digital classes in addition to following technological developments is also to welcome the golden generation in the industrial revolution 4.0. Introducing technology to students, how to use the technology, as well as how to learn at school using technology properly and correctly. 2). The advantages of implementing a digital classroom are that it generates new enthusiasm, a new learning atmosphere for students, makes it easier for students to accept learning, and adds insight. For teachers, it makes it easier to deliver material to students, makes it easier to work on grades and others. The shortcomings that are felt by both teachers and students are new habits that demand to be able to operate digital media, especially laptops, need to learn and also habituation from teachers and students so that the implementation of digital classes can run as expected. In terms of infrastructure, the shortcomings in implementing digital classes are when there is a power outage, it certainly interferes with the teaching and learning process using digital classes. Although the material can be searched in e-books which do not need to use the internet, teachers often search via google, teacher's room, etc. to update learning materials.